Effects of irrigated and dryland cultivation on soil carbon, nitrogen and phosphorus in northeastern Colorado - Sinton, Penelope J., author; Burke, Ingrid C., advisor; Kelly, Eugene F., committee member; Peterson, Gary A., 1940-, committee member; Lauenroth, William K., committee member (Colorado State University. Libraries, 2001)
I investigated the effects of irrigated and fertilized com agriculture on soil C, N and P in northeastern Colorado as they compare to dryland wheat-fallow fields and native rangelands in the semiarid shortgrass steppe of northeastern Colorado. Three replicates each of native rangeland, dry land wheat-fallow, and irrigated corn fields located in or adjacent to the Pawnee National Grasslands were selected for this study. I measured potentially mineralizable C and N from 0-15cm in the soil profile, particulate organic matter (POM) C and Nin the upper 30cm, total and NaHC03-P to a depth of 105cm, and total soil C and N to a depth of 195cm in the soil profile. Irrigated corn fields contained significantly lower mineralizable, POM, and total C and N than rangelands in the upper 5cm of soil. Com fields also had significantly greater NaHCOrP content than rangelands or wheat-fallow fields to a 1-meter depth in the soil. Wheat-fallow fields had significantly less potentially mineralizable and POM C and N than rangelands or corn fields in the upper 5cm of soil. Cumulative losses of total C and N in wheat-fallow fields extended to depths of 75cm or more. There were no significant differences in total P among land use types. Differences in C and N between corn and wheat-fallow fields are likely due to differences in the quantity of plant residue inputs. The distribution of C, N and NaHC03-P through the soil profile in corn fields also differed from rangelands. Soil C, N and NaHC03-P in the soil profile of rangelands decreased from the surf ace down, whereas in com fields C, N and NaHC03-P increased from the surf ace to 30cm and then decreased. Distribution of C, N and P in corn fields may be due to leaching of C or N or decomposition changes in the soil profile. In wheat-fallow fields, C, N and NaHC03-P showed a more uniform distribution in the upper 30cm of soil than rangelands, likely due to tillage practices that mix the upper soil layers in wheat-fallow fields. These results indicate that irrigated and fertilized corn crops in this region of the semiarid shortgrass steppe depletes pools of C and N at the soil surf ace but does not cause a change in C or N below the 5cm layer of soil. The differences in amount and distribution of C and N observed in this study among dryland wheat-fallow and irrigated corn fields indicate that the type of crop grown in this region should be an important consideration for regional studies that evaluate C and N changes due to cultivation.
Keywords: Soil mineralogy -- Colorado; Irrigation farming -- Colorado; Dry farming -- Colorado